Use of Semantic Web technologies in Knowledge Management - Jovanovik, Milos; Trajanov, Dimitar; Stojanov, Riste; Apostolski, Vladimir (Institute of Informatics, Skopje, Macedonia, 2010)
The fast technology development causes exponential increase of the number of information available to the people. But people do not to extract useful conclusions from all the information served, simply because they are either overloaded or uninterested about certain topics. By their nature, people are slow, unreliable, they forget and make errors while interpreting information. Machines, on the other hand, are much more effective in terms of speed, processing power and reliability, making them suitable for managing with human knowledge. The idea is to introduce systems for knowledge management, organization and interpretation by computers, which will raise the human-computer interaction level and improve distribution of knowledge according to individual needs. Systems capable of gathering, sharing, learning and interpreting stored information are referred to as Semantic Knowledge Management Systems. In this paper, we analyze traditional knowledge management software systems and then describe our effort to implement such knowledge management system that is fueled by available Semantic Web technologies. Its architecture is given in details, as well as the platform on which our experiments are performed. At the end of the paper we conclude that semantic knowledge management systems open a new field of opportunities for research and further realization of the idea about the Semantic Web.